2009
DOI: 10.1080/13506120902879269
|View full text |Cite
|
Sign up to set email alerts
|

Excessive fibrinolysis in AL-amyloidosis is induced by urokinae-type plasminogen activator from bone marrow plasma cells

Abstract: Activation of fibrinolysis system and excessive fibrinolysis are observed in monoclonal antibody light chain (AL)-amyloidosis. However, the mechanisms by which activation of fibrinolysis occurs in AL-amyloidosis have not been fully elucidated. To determine whether urokinase type-plasminogen activator (uPA), an important activator of fibrinolytic system, contributes to the activation of fibrinolytic system in AL-amyloidosis, we immunohistologically examined uPA in bone marrow plasma cells. More than 90% of bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…In this study, a clinically significant VTE was seen in only 71 patients, although it is possible that additional patients had undetected venous or arterial thrombi, as asymptomatic patients were not screened for the presence of a thrombus. Activation of fibrinolysis may also lead to D‐dimer elevation, as the fibrinolytic pathway is known to be active in AL amyloidosis and could be the mechanism by which many patients have an increased bleeding risk . Additionally, the elevation in D‐dimer may be related to the underlying endothelial dysfunction and abnormal vascular morphology found in AL amyloidosis .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In this study, a clinically significant VTE was seen in only 71 patients, although it is possible that additional patients had undetected venous or arterial thrombi, as asymptomatic patients were not screened for the presence of a thrombus. Activation of fibrinolysis may also lead to D‐dimer elevation, as the fibrinolytic pathway is known to be active in AL amyloidosis and could be the mechanism by which many patients have an increased bleeding risk . Additionally, the elevation in D‐dimer may be related to the underlying endothelial dysfunction and abnormal vascular morphology found in AL amyloidosis .…”
Section: Discussionmentioning
confidence: 65%
“…The organs most commonly affected in this disease are the kidneys, heart, liver, and nerves. In addition, dysregulated coagulation, with bleeding and clotting complications, has also been reported . Bleeding diatheses in AL amyloidosis are often related to factor deficiencies, with Factor X deficiency being the most widely studied .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrinolysis is known to be exacerbated in patients with systemic AL amyloidosis ( 3 , 6 - 10 ). A few studies have reported elevated levels of plasmin-α2-plasmin inhibitor complex (PIC) in patients with systemic amyloidosis ( 3 , 6 , 8 , 10 ). However, whether or not the elevation of PIC is specific to patients with systemic AL amyloidosis or common in patients with serum monoclonal protein is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Amyloidogenic mutated transthyretin (TTR) is the most common FAP-related protein worldwide [1]. Several studies reported coagulation factor X (FX) deficiency and excessive fibrinolysis in immunoglobulin light chain amyloidosis (AL amyloidosis) patients [2][3][4]. However, few have investigated coagulation and fibrinolysis in FAP.…”
Section: Introductionmentioning
confidence: 99%